Examining the influence of static application security testing on the overall security of web applications - Еленгаупт, В. В. (ХНУРЕ, 2023)
With the exponential growth of the internet and the rising reliance on web applications, ensuring their security has become a critical concern for organizations and individuals alike. Web applications are often vulnerable to a range of cyber threats, including data breaches, unauthorized access, and other malicious activities. In this context, Static Application Security Testing (SAST) has emerged as a crucial technique for strengthening web application security by identifying and mitigating potential vulnerabilities during the development stage.